IMPROVING ENGLISH WRITING SKILL BY UTILIZING QUIZIZZ AS A TECHNOLOGY-BASED ASSESSMENT - Veysa Malvado; Entika Fani Prastikawati; Wiyaka Wiyaka (LINGUAMEDIA Journal, 2021)
The insertion of technology in English language teaching has been massively implemented by the English teachers during the pandemic Covid-19. This massive use of technology is also found during the assessment process. On the other hand, students still find difficulties in composing English texts. To fill this gap, this current study is investigating the current use of Quizizz as a technology-based assessment to improve the students’ writing skill during the English teaching and learning in the pandemic Covid-19. By deploying a pre-experimental research design, this study involved sixteen eighth grade students in SMP Negeri 13 Semarang as the subjects. To obtain the data, a writing test was employed in term of pre-test and post-test. The result shows that students’ writing skill was improved well after Quizizz was implemented regularly during the English teaching and learning. This result implies that Quizizz as a technology-based assessment helps the students to enhance their writing skill.